Dynamic performance of terahertz quantum cascade laser with double optical feedbacks: Role of the external cavity - Y. Mao; W. Feng; Y.H. Zheng; C. Wang; J.C. Cao (Results in Physics, 2023)
The dynamic performance of a terahertz (THz) quantum cascade laser (QCL) with double optical feedbacks (DOFs) is carefully studied within the framework of single-mode rate equations. The results have shown that the system displays three types of nonlinear dynamic phenomena under the control of different feedback strengths, which are envelope oscillations, spiking oscillations, and high-frequency small-amplitude oscillations, respectively. The fundamental frequency of oscillation is related to the ratio of the round-trip times from two external cavities and the ratio of their feedback strengths. By solving the steady-state equations, we find that the high-frequency, small-amplitude oscillations arise because a pair of modes appear at almost the same point. The output performance of THz QCL system is also studied with square wave signal modulation. The results show that the fundamental frequency of oscillation at the output is only related to the frequency of the square wave signal. And low frequency fluctuations (LFFs) dynamics can be excited by combination of DOFs and adjusting the duty cycle of the square wave signal. This work provides a novel insight into high data-bit THz communication based on QCLs.